Awareness, Acceptance, and Understanding of University Vision, Mission, College Goals, and BSIT Objectives of Laguna State Polytechnic University Stakeholders towards its VMGO - Michael Del Rosario Aquino, John; Rivano, Enrico (ASEAN Journal of Education, 2023)
The center of all universities’ operations must be the vision, mission, goals, and objectives (VMGO). These statements have a vital role in the process of the institutions, and it applies to all types of organizations, both public and private. This research was conducted to determine the stakeholders’ level of awareness, acceptance and understanding of the VMGO of Laguna State Polytechnic University, College of Industrial - Sta. Cruz, Campus and its relationship. This study employed a quantitative descriptive method, using a questionnaire with a total of 158 respondents among stakeholders. The respondent’s rating in the survey ranged from highest to lowest of the magnitude, to identify the respondents’ level of awareness and was analyzed as shown in the results and discussions section. The level of awareness, acceptance, and understanding in the University’s VMGO are extremely accepted by the respondents among all stakeholders. There is a significant relationship between the awareness and acceptance and understanding which was pegged at 0.841 correlation coefficient and having p value of .036. It is recommended that LSPU continue to promote the awareness, acceptability, and understanding of the LSPU VMGO for the continuous development of the university.